Los culpables : recuerdos de la guerra, 1936-1939 / Juan Perea Capulino ; edición a cargo de Mauricio y Álvaro Perea y Juan Barceló - Perea, ÁlvaroPerea, MauricioBarceló, Juan; Perea Capulino, Juan (1890-1967) (Tramontana; 17)
Índice onomástico